Westminster College of Chemistry and Pharmacy - Wills, George S. V. (A Manual of Vegetable Materia Medica, 1886)
Advertisement for the Westminster College of Chemistry and Pharmacy with illustration of the school's building. This manual identifies plants used for medicinal purposes. The focus is on plants that can be acquired through commerce in Britain and are illustrated as they would have been imported and bought, for example the opium is illustrated as a processed capsule wrapped in a poppy leaf instead of the poppy plant itself. Authored by George Sampson Valentine Wills (1849-1932). Wills was the founder and Director of the Westminster College of Chemistry and Pharmacy in London. The school was established in 1872 to train druggists for examinations by the Pharmaceutical Society of Great Britain, the regulating body established in 1841.
Keywords: Botany, Medical; Medicinal plants; Materia medica, Vegetable; Universities and colleges